2022
DOI: 10.1590/s0004-2803.202203000-69
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Capnography for Respiratory Monitoring of Patients During Routine Colonoscopy With Room-Air and Carbon Dioxide Insufflation

Abstract: Background: Capnography and carbon dioxide (CO2) insufflation during gastrointestinal endoscopy under sedation are associated with safety and comfort improvements, respectively. Capnography can provide early detection of apnea and hypoxemia, whereas CO2 insufflation causes lower periprocedural discomfort. This is the first study to report the application of volumetric capnography in colonoscopy. Objective: This study aimed to evaluate the use of volumetric capnography with room air (RA) and CO2 insufflation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…[ 17 ] These complications attributed to sedation may exceed technical complications by a factor of 10. [ 18 ] Previous studies indicated that patients would be helped by shorter discharge time and reduced sedation with a patient–control sedation protocol, either with propofol–alfentanil PCS or midazolam–pethidine regimens. [ 19 ] In our current study, the PCAS procedure administered with remifentanil and propofol led to a faster recovery time compared to the TIVA approach.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] These complications attributed to sedation may exceed technical complications by a factor of 10. [ 18 ] Previous studies indicated that patients would be helped by shorter discharge time and reduced sedation with a patient–control sedation protocol, either with propofol–alfentanil PCS or midazolam–pethidine regimens. [ 19 ] In our current study, the PCAS procedure administered with remifentanil and propofol led to a faster recovery time compared to the TIVA approach.…”
Section: Discussionmentioning
confidence: 99%
“…For gastrointestinal endoscopy, routine anesthesia monitoring includes blood pressure and oxygen saturation. However, statistics show that the probability of respiratory complications during anesthesia is as high as 20-30% [1][2][3][4]. Therefore, it is necessary to develop a low-cost device for real-time and continuous-concentration endtidal carbon dioxide (CO 2 ) monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…For gastrointestinal endoscopy, routine anesthesia monitoring includes blood pressure and oxygen saturation. However, statistics show that the probability of respiratory complications during anesthesia is as high as 20-30% [1][2][3][4]. Therefore, it is necessary to develop a low-cost device for real-time and continuous concentration of end-tidal carbon dioxide monitoring.…”
Section: Introductionmentioning
confidence: 99%